Fasciolariidae (Gastropoda: Neogastropoda) of French Guiana and nearby regions, with descriptions of two new species and comments on marine zoogeography of northeastern South America - Lyons, William G.; Snyder, Martin Avery (Zootaxa, 2019)
The fasciolariid fauna from two expeditions to French Guiana is examined and augmented with published records and material of other collections from the Guianas and northeastern Brazil. Twelve species of Fasciolaria and Aurantilaria (Fasciolariinae), Aristofusus, Lyonsifusus and Fusinus s.l. (Fusininae), and Lamellilatirus and Polygona (Peristerniinae) are reported and discussed. Nine species are represented in expedition collections, and reports of three other species are evaluated. Two morphologically distinct species of Lamellilatirus are described as new; type localities of both are off French Guiana, 114–118 m. Ten Guianan fasciolariids range variously northward to Caribbean South America and the Lesser Antilles and southward to Ceará, Brazil; one other extends into the northern Caribbean, and one extends southward to Rio de Janeiro, Brazil.